An infant with X‐linked anhidrotic ectodermal dysplasia with immunodeficiency presenting with Pneumocystis pneumonia: A case report - Miwako Toyohara (Wiley, 2021)
Abstract Pneumocystis jirovecii pneumonia associated with primary immunodeficiency should be considered in infants with slowly progressing cyanosis, even without fever or respiratory symptoms. Genetic counseling is crucial for incontinentia pigmenti families in advance of pregnancy because lethal infections can occur before the diagnosis of X‐linked anhidrotic ectodermal dysplasia with immunodeficiency.